(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
This paper represents a preliminary analysis of a group of bone artifacts found at central district in Nora (Cagliari), during the excavations of the University of Milan. This group includes hair pins, sewing needles, and makeup applicators. The typological classification of these objects shows the real chronology of the context, the technology of bone materials and the women customs in ancient Rome. The bone-working study is still in a preliminary stage of research, and every new analyzed context can provide useful data to understand this craft.